2019
DOI: 10.3390/rs11070765
|View full text |Cite
|
Sign up to set email alerts
|

A SAR Dataset of Ship Detection for Deep Learning under Complex Backgrounds

Abstract: With the launch of space-borne satellites, more synthetic aperture radar (SAR) images are available than ever before, thus making dynamic ship monitoring possible. Object detectors in deep learning achieve top performance, benefitting from a free public dataset. Unfortunately, due to the lack of a large volume of labeled datasets, object detectors for SAR ship detection have developed slowly. To boost the development of object detectors in SAR images, a SAR dataset is constructed. This dataset labeled by SAR e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
220
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(220 citation statements)
references
References 39 publications
0
220
0
Order By: Relevance
“…China's Gaofen-3 satellite SAR and Sentinel-1 SAR datasets as the main data sources used in this study, with a total usage of 102 Gaofen-3 images and 108 Sentinel-1 SAR images [23] Figure 3. In addition, labelling tools are used to label the vessel position and for classification.…”
Section: Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…China's Gaofen-3 satellite SAR and Sentinel-1 SAR datasets as the main data sources used in this study, with a total usage of 102 Gaofen-3 images and 108 Sentinel-1 SAR images [23] Figure 3. In addition, labelling tools are used to label the vessel position and for classification.…”
Section: Datasetmentioning
confidence: 99%
“…Gaofen-3 satellite SAR and Sentinel-1 SAR datasets as the main data sources used in this study, with a total usage of 102 Gaofen-3 images and 108 Sentinel-1 SAR images[23]. The SAR dataset includes 43,819 ship data slices.…”
mentioning
confidence: 99%
“…The dataset used in this paper is a SAR dataset for ship detection published by the Digital Earth Laboratory of the Aerospace Information Research Institute, Chinese Academy of Sciences [50]. There are 102 GaoFen-3 images and 108 Sentinel-1 images that are used to constructed the dataset.…”
Section: Dataset Descriptionmentioning
confidence: 99%
“…where ( )is the original source signal, �( )is the separated signal, is the sample index and N is the number of samples of the signal.A better performance of the matched filter is shown by a higher the value of PSNR with minimum value of RMSE.To demonstrate the performance of the proposed model, multispectral image sample data is considered. (d,f,g,i) are the cropped ship chips from the Gaofen-3 images with Ultrafine Strip (UFS) imaging mode (Wang, et al, 2019) In a multispectral dataset, the band information is reported as the centre wavelength value that represents the centre point value of the wavelengths. Simulations are performed on noisy mixed sample signal data on Matlab® R 7.9 on a core i7 2.2 GHz PC using the USFFT software package.…”
Section: Applications: Radar/satellite Signal Denoisingmentioning
confidence: 99%